Contemporary British literature and urban space : after Thatcher - Duff, Kim (New York : Palgrave Macmillan, 2014)
"Contemporary British Literature and Urban Space distils the possibilities for a new way of thinking about space and identity that challenges the seemingly innocuous methods of spatial acquisition and ownership that are inherently tied to Thatcherite notions of privatization. With this in mind, Kim Duff's study examines how Iain Sinclair, Julian Barnes, Irvine Welsh, JG Ballard, Monica Ali, Hanif Kureishi, Alan Hollinghurst, and Will Self write, and rewrite, the city as they capture, subvert, and uncover the tensions inherent in the transformation of British urban space by proposing an understanding of alternative spaces (including the new spatial possibilities of television and communications technology) and emergent citizens, identities, and communities that developed, and continue to develop, as a result of Thatcherism. "--
Introduction: The Spatial Turn: Dialectics of Space and Identity 1.'The Script That Has Been Eradicated from the Street': Iain Sinclair's Lights Out for the Territory, Julian Barnes's England England, and the Spaces of English Heritage 2.'House Arrest': Irvine Welsh's Trainspotting, JG Ballard's High Rise, Thatcherite Council Estates, and the New Under-Class 3.Space, Production, and Identity: Monica Ali's Brick Lane, Hanif Kureihi's My Beautifult Laundrette, and Powellite Englishness 4.The Spaces of the Thatcherite Body: Alan Hollinghurst's The Line of Beauty and Will Self's Dorian Conclusion End Notes Works Cited Index.
Includes bibliographical references (pages 174-181) and index.
Keywords: Thatcher, Margaret -- Influence; English fiction -- 20th century -- History and criticism; English fiction -- 21st century -- History and criticism; City and town life in literature; Space and time in literature; Identity (Psychology) in literature; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; LITERARY CRITICISM / Semiotics & Theory